Developing mathematics teachers' pedagogical content knowledge through lesson study : a multiple case study at a time of curriculum change - Ní Shúillebháin, Aoibhinn (Trinity College (Dublin, Ireland). School of Education, 2015)
This research was interested in investigating a model of in-school professional development that would support teachers in their practices and in their learning, particularly within a backdrop of curriculum reform. Lesson study (Lewis, Perry, & Murata. 2006) was identified as a model of professional development which would provide structure for collaboration within a teacher community where teachers could be provided with opportunity to develop their knowledge through participation. In contributing to advancing knowledge, this research offers a detailed analysis of: how teachers’ pedagogical content knowledge was enhanced both in terms of detailing how teachers employed and enhanced their knowledge, and in detailing the mechanisms within lesson study which contributed to teacher learning by mapping that knowledge to an existing framework as suggested by Ball, Thames & Phelps, (2008).
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin